Traditional Chinese Medicine for Refractory Nephrotic Syndrome: Strategies and Promising Treatments. (4th January 2018) - Wang, Xiao-Qin; Wang, Lan; Tu, Yuan-Chao; Zhang, Yuan Clare
Abstract : Refractory nephrotic syndrome (RNS) is an immune-related kidney disease with poor clinical outcomes. Standard treatments include corticosteroids as the initial therapy and other immunosuppressants as second-line options. A substantial proportion of patients with RNS are resistant to or dependent on immunosuppressive drugs and often experience unremitting edema and proteinuria, cycles of remission and relapse, and/or serious adverse events due to long-term immunosuppression. Traditional Chinese medicine has a long history of treating complicated kidney diseases and holds great potential for providing effective treatments for RNS. This review describes the Chinese medical theories relating to the pathogenesis of RNS and discusses the strategies and treatment options using Chinese herbal medicine. Available preclinical and clinical evidence strongly supports the integration of traditional Chinese medicine and Western medicine for improving the outcome of RNS. Herbal medicine such as Astragalus membranaceus, Stephania tetrandra S. Moore, and Tripterygium wilfordii Hook F can serve as the alternative therapy when patients fail to respond to immunosuppression or as the complementary therapy to improve therapeutic efficacy and reduce side effects of immunosuppressive agents. Wuzhi capsules ( Schisandra sphenanthera extract) with tacrolimus and tetrandrine with corticosteroids are two herb-drug combinations that have shown great promise and warrant further studies.